Melt grafting of N-carbamyl maleamic acid onto linear low-density polyethylene - Ciolino, Andrés Eduardo (2002)
The grafting of N-carbamyl maleamic acid (NCMA) onto linear low-density polyethylene (LLDPE) was carried out with different concentrations of 2,5-dimethyl-2,5-di(tert-butylperoxy) hexane (DBPH) as an initiator. The modification process was performed in the molten state with a Brabender mixer. All the materials were characterized with Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry, and melt rheology. The analysis of the FTIR spectra indicated that the grafting efficiency increased with the concentration of both NCMA and DBPH. The calorimetric experiments showed that the modification process did not noticeably alter the enthalpy of fusion of LLDPE, whereas the melting temperature of the modified polymers was slightly lower than that corresponding to the original LLDPE. The rheological response of the molten polymers, determined under dynamic shear flow at small-amplitude oscillations, indicated that the modification process induced crosslinking of the chains. Both the dynamic viscosity and elastic modulus of the modified LLDPE increased with the concentration of NCMA and DBPH, showing that larger molecules were generated during the modification process.